The Pengembangan Perangkat Pembelajaran RBL-STEM untuk Meningkatkan Kreativitas Siswa dalam Inovasi Teknologi Ramah Lingkungan: Transformasi Kardus Bekas Menjadi Sapu Elektrik - Aning Setianingsih; Rina Sugiarti Dwi Gita; Eges Triwahyuni (Postgraduate, University of Mataram, 2026)
This study focuses on the development of RBL–STEM learning materials that integrate research-based learning and STEM principles to foster students’ creativity through an eco-friendly technological innovation project, specifically the transformation of used cardboard into a functional electric broom. The development used the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation, and this study produced a set of comprehensive learning materials, including instructional modules, student worksheets, project media, and creativity assessment instruments. Expert validation confirmed that the developed materials were valid, while responses from teachers and students indicated a high level of practicality. Empirical implementation demonstrated a moderate improvement in students’ learning outcomes, as reflected by an average N-gain score of 0.5617, and evidenced the students’ ability to generate creative and functional electric broom prototypes. These findings contribute to the field of science education by providing an empirically validated RBL–STEM learning framework that promotes creativity through sustainable technological innovation at the elementary school level. The significance of the study is reflected in its contribution to enhancing students’ creativity, strengthening their understanding of scientific concepts, and fostering environmental awareness through research- and engineering-oriented learning experiences. The developed RBL–STEM learning materials were empirically demonstrated to be feasible and effective in supporting innovative science instruction at the elementary school level.